TECHNIQUES FOR BLOGGERS WORKING WITH A MALE TARGET AUDIENCE ON THE EXAMPLE OF RUSSIAN BLOGGER DMITRY “GOBLIN” PUCHKOV - L. G. Akhmaeva (Вестник университета)
The concept of “blogger” as an integral and important part of “influence marketing”, as well as techniques and examples of competent work with the segment and advertising integration on the example of Russian blogger Dmitry “Goblin” Puchkov has been considered. The marketing mechanisms that the brand generally uses when attracting bloggers to promote the product have been reviewed. A number of methods of competent work of blogger Dmitry “Goblin” Puchkov with a male target audience has been highlighted, the resources on which he carries out his activities and the content contained on them have been considered. Recommendations to marketers aimed at an adult male audience for the successful development of channels with subsequent placement of advertising content have been given.